Transcriptome annotation reveals minimal immunogenetic diversity among Wyoming toads, Anaxyrus baxteri - Kara B. Carlson; Dustin J. Wcisel; Hayley D. Ackerman; Jessica Romanet; Emily F. Christiansen; Jennifer N. Niemuth; Christina Williams; Matthew Breen; Michael K. Stoskopf; Alex Dornburg; Jeffrey A. Yoder (Conservation Genetics, 2022)

Angiopoietin-like protein 2 regulates endothelial colony forming cell vasculogenesis - Matthew R. Richardson; Emilie P. Robbins; Sasidhar Vemula; Paul J. Critser; Catherine Whittington; Sherry L. Voytik-Harbin; Mervin C. Yoder (Angiogenesis, 2014)

Amyloid pathway-based candidate gene analysis of [11C]PiB-PET in the Alzheimer’s Disease Neuroimaging Initiative (ADNI) cohort - Shanker Swaminathan; Li Shen; Shannon L. Risacher; Karmen K. Yoder; John D. West; Sungeun Kim; Kwangsik Nho; Tatiana Foroud; Mark Inlow; Steven G. Potkin; Matthew J. Huentelman; David W. Craig; et al. (Brain Imaging and Behavior, 2012)

Comparative water balance profiles of Orchidaceae seeds for epiphytic and terrestrial taxa endemic to North America - Jay A. Yoder; Samantha M. Imfeld; Derrick J. Heydinger; Chloé E. Hart; Matthew H. Collier; Kevin M. Gribbins; Lawrence W. Zettler (Plant Ecology, 2010)

Relationships of Exodontiella , a non‐alysiine, exodont member of the family Braconidae (Insecta, Hymenoptera) - Robert A. Wharton; Matthew J. Yoder; Joseph J. Gillespie; John C. Patton; Rodney L. Honeycutt (Zoologica Scripta, 2006)
The placement of Exodontiella Wharton is re‐examined in light of the discovery of four additional individuals. Genomic DNA was extracted from one of the individuals, the D2 expansion segment of the 28S rRNA gene was sequenced, and the sequence compared to selected taxa within the Braconidae. Based on the molecular data and the morphological study, Exodontiella is formally transferred from the Opiinae to the Gnamptodontinae. The genus and its included species are redescribed.

Predicted Secondary Structure for 28S and 18S rRNA from Ichneumonoidea (Insecta: Hymenoptera: Apocrita): Impact on Sequence Alignment and Phylogeny Estimation - Joseph J. Gillespie; Matthew J. Yoder; Robert A. Wharton (Journal of Molecular Evolution, 2005)